Organizational misbehaviour - Ackroyd, Stephen; Thompson, Paul, 1951 January 1-; Sage eBooks (London : SAGE, 1999)
This text is a contemporary analysis of the many different forms of organizational subversion. Going beyond the anecdotal approach, it provides a critical overview and explores subjects such as absenteeism, humour and the politics of sexuality.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Organizational behavior; Work environment; Electronic books